In situ expression of β1, β3 and β4 integrin subunits in non-neoplastic endothelium and vascular tumours - Mechtersheimer, Gunhild; Barth, Thomas F. E.; Hartschuh, Wolfgang; Lehnert, Thomas; Möller, Peter (Virchows Archiv, 1994)
Endothelial cells play an important role in adhesive interactions between circulating cells and extracellular matrix proteins. In vitro studies have shown that many of these processes are mediated by a superfamily of αβ heterodimeric transmembrane glycoproteins called integrins. The distribution patterns of β1, β3 and β4 integrin subunits in endothelial cells (EC) in situ were examined immunohistochemically on serial forzen sections of a wide range of non-neoplastic tissues and of vascular tumours, both benign and malignant. Expression of the β1 subunit was a constitutive feature of EC. Among the β1-associated α subunits, α5 and α6 were broadly distributed in EC, irrespective of vessel size and microenvironment. The α3 subunit displayed intermediate levels of expression with a slight preference for small vessel EC. Presence of α1 was confined to EC of capillaries and venules/small veins. Expression of α2 in EC was inconsistent. With rare exceptions, the α4 chain was absent in EC. The β3 and αv subunits were expressed in most EC, though not always concomitantly. In contrast to the β1 chain, however, these integrin subunits were absent in EC of glomerular capillaries and were expressed variably in sinusoidal EC. The β4 chain was evenly present in the great majority of EC, except for those of large vessels. In vascular tumours, the patterns of β1 and α1 to α6 subunit expression generally corresponded to those found in their non-neoplastic counterparts. Expression of β3, αv and β4 chains, however, decreased in neoplasia, especially in angiosarcomas. These data show that EC dispose of broad and at the same time differential repertoires of integrin subunits that presumably reflect vessel-type associated functional differences among these cells. In vascular tumours, the orthologous distribution patterns of β1 and α1 to α6 chains are conserved in most instances while the amounts of β3, αv and β4 subunits expressed in EC tend to decrease in the course of malignant transformation.
Gesehen am 22.07.2025